2005
DOI: 10.1007/s00134-005-2841-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in muscle tissue oxygenation during stagnant ischemia in septic patients

Abstract: After hemodynamic stabilization thenar muscle tissue oxygen saturation during stagnant ischemia decreases slower in septic shock patients than in patients with severe sepsis or localized infection and in healthy volunteers. During ICU stay and improvement of sepsis the muscle tissue deoxygenation rate increases in survivors of both septic shock and severe sepsis and was correlated with SOFA score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
80
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 18 publications
8
80
1
3
Order By: Relevance
“…In particular, the descending slope of StO 2 reflects oxygen diffusion from microvessels to cells during stagnant ischemia (i.e. when metabolic demand and oxygen consumption are equivalent) [15]. Ascending slope of StO 2 represents the reperfusion phase after an ischemic challenge and depends on the ratio between oxygen delivery and oxygen consumption (DO 2 /VO 2 ), microvascular recruitment, and compliance.…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…In particular, the descending slope of StO 2 reflects oxygen diffusion from microvessels to cells during stagnant ischemia (i.e. when metabolic demand and oxygen consumption are equivalent) [15]. Ascending slope of StO 2 represents the reperfusion phase after an ischemic challenge and depends on the ratio between oxygen delivery and oxygen consumption (DO 2 /VO 2 ), microvascular recruitment, and compliance.…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…The observation that their baseline values of tissue saturation in muscles are reduced [39,40] has not been confirmed in other studies [41,42]. Pareznik and co-workers [42] have demonstrated that the rate of tissue saturation decreases during the flow arrest in the limb was lower in septic shock patients than in the remaining patients, which was explained by impaired abilities of oxygen extraction and its consumption in tissues. In survivors, the restoration of the rate of saturation decreases during the VOT was observed.…”
Section: Use Of Oximetry For Evaluation Of Microcirculation and Oxygementioning
confidence: 90%
“…There is mounting evidence about the microcirculatory derangement in the critically ill mainly in septic shock [53]. Due to the endothelial dysfunction [54], glycocalyx layer degradation [55] and pathological cell-endothelial interactions [56], a condition termed 'microcirculatory shock' can develop, which can be defined as 'the failure of microcirculation to support tissue perfusion and oxygenation, despite normal systemic hemodynamics' [57]. Under physiological circumstances, a dens capillary system forms the microcirculation, with low heterogeneity in perfusion.…”
Section: Microcirculationmentioning
confidence: 99%